ANALISIS KOMPETENSI PETANI JAGUNG HIBRIDA DALAM STRATEGI KEWIRAUSAHAAN PADA MASA PANDEMI COVID-19 DI KECAMATAN NAPABALANO KABUPATEN MUNA - Siti Rahma Mujur; Usman Rianse; Sitti Nur Isnian (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2022)
This study aims to: find out how the competence of hybrid corn farmers in entrepreneurial strategies during the covid-19 pandemic in Napabalano District, Muna Regency. This research was conducted in Napabalno District, Muna Regency from November to December 2020. Informants were determined by purposive sampling with a total of 10 farmers consisting of key informants and supporting informants with categorization considerations. The data in this study uses exploratory qualitative data analysis. The research data shows that the knowledge competence of farmers in Napabalano District, Muna Regency has knowledge of work ethic including (1) independent, independent knowledge possessed by farmers during the covid19 pandemic. Farmers continue to carry out their farming by working independently or working alone without the help of others or family assistance. (2) discipline, the knowledge of farmers' discipline during the covid19 pandemic will continue to carry out domestic activities the same as before and after the covid19. (3) they like to work hard, their knowledge continues to carry out agricultural activities, namely planting hybrid corn plants despite the known fact that income has decreased due to covid19. (4) being responsible, the knowledge in question is that they dare to take risks against the business they do during the covid19 pandemic.